Underground Natural Gas Storage: Enhancing Flexibility in Brazil’s Electricity Sector - Almeida, José Ricardo Uchôa Cavalcanti; Losekann, Luciano; de Almeida, Edmar; Raeder, Francisco (New Energy Exploitation and Application, 2025)
Supply flexibility is an essential attribute for the development of natural gas markets. In countries that have a mature market, gas storage capacity is used to deal with variations in demand. In Brazil, the natural gas market is still developing, and flexibility is an important challenge. In most of the more mature natural gas markets, the seasonality of demand is closely linked to temperature (harsh winter), and flexibility mechanisms were developed for this purpose. In Brazil, demand volatility is determined by the thermoelectric segment, as gas thermal plants have a complementary role to the hydroelectric park. This situation has brought challenges to the development of the gas market in Brazil. Thus, flexibility mechanisms can generate significant efficiency gains by avoiding underutilization of infrastructure. The article analyzes the Underground Storage of Natural Gas (UGS) as a “flexibility” tool, suitable for the Brazilian market to guarantee a balance of supply versus demand without deficits and in an optimized way, considering the randomness of gas demand. The economic value added by UGS to the electricity sector is illustrated through a case study of a natural gas thermoelectric plant that uses pre‑salt associated gas. Thus, using the Monte Carlo simulation method, this study demonstrated the economic value for the Brazilian electricity sector of contracting underground natural gas storage capacity to be used in the dispatch of natural gas‑fired thermal power plants as part of a trade‑off with liquefied natural gas (LNG).